Cost-effectiveness of treatment with finerenone in mild to advanced stage chronic kidney disease patients with type 2 diabetes from a societal perspective - Maarten J Postma; Stephan J L Bakker; Sara Wilhelmien Quist; Jeanni van Loon; Michal Pochopién; Jeroen Paulissen (BMJ Public Health, 2025)
Introduction One in three patients with type 2 diabetes (T2D) suffers from any stage of chronic kidney disease (CKD), a chronic illness associated with a high global burden that impacts not only the healthcare system but also societal costs. Addition of finerenone to the standard of care (SoC) for patients with advanced CKD and T2D has been shown to be cost-effective by reducing healthcare and societal costs. This analysis explores the cost-effectiveness of finerenone in patients with CKD (stages 1–4 with albuminuria) associated with T2D from a societal perspective, as broader societal costs are a crucial consideration in managing chronic illnesses.Research design and methods The validated FINE-CKD model was populated with data from the pooled FIDELITY analysis (ie, a patient population with early-to-late stage CKD associated with T2D) to investigate the cost-effectiveness of the addition of finerenone to SoC compared with SoC alone, from a Dutch societal perspective. Sensitivity analyses were conducted to evaluate the impact of parameter uncertainty on the robustness of the model.Results Our analysis shows that by adding finerenone to SoC, patients with mild to severe stage CKD and T2D gain 0.14 quality-adjusted life years (QALYs) compared with SoC alone, mainly due to a reduction in renal and cardiovascular events. The societal costs of these events are considerable (ie, €8481 and €9799 per patient over a lifetime in the finerenone and SoC arm, respectively), showing the relevance of a societal perspective in chronic diseases. Overall, finerenone leads to savings of €2713 per patient over a lifetime. Therefore, the addition of finerenone to SoC emerges as the dominant treatment option when compared with SoC alone. The sensitivity analysis shows that finerenone has a 62.3% chance to be dominant and an 83.8% chance to be cost-effective, considering a willingness-to-pay threshold of €20 000/QALY.Conclusions This study highlights the burden that chronic diseases impose on healthcare systems and society, emphasising the relevance of incorporating a societal perspective in cost-effectiveness analyses. The analysis estimates that adding finerenone to SoC treatment for patients with mild to advanced CKD associated with is cost-effective from a healthcare and societal perspective.